Ab Initio Calculation of Vibrational Frequencies of ZnSe and the Raman Spectra - Rosli, AN; Zabidi, NA; Abu Kassim, H (Amer Inst Physics, 2024)
The single layer of ZnSe has been studied to understand the structure using density functional theory. The vibrational frequencies of several cluster of ZnSe have been calculated when the Kohn-Sham equation solved at the ground state energy. We have done the calculation for 34 models of ZnSe clusters but only the stable molecules will be discussed. The bond length, Fermi energy and binding energy of ZnSe clusters have been calculated. The experimental result of single layer of ZnSe shown by Nesheva et. al. using different thickness of layers until 1 mu m [1]. The Raman spectra of ZnSe shown several peak for different thickness. In this paper, we will show the comparison of our calculated result with the experimental Raman spectra to show the existent of cluster.